Eimeria rangiferis (Protozoa: Eimeriidae) reported from caribou in Ameralik, West Greenland - Skírnisson, Karl; Cuyler, Christine (Rangifer, 2015)
In recent decades the native Barren-ground caribou (Rangifer tarandus groenlandicus) south of the Godthaabs fjord (Nuup Kangerlua fjord) in West Greenland have mixed with semi-domesticated Norwegian reindeer (R. t. tarandus) imported in 1952 from Finnmark Norway and released onto the range of the Ameralik caribou population. Fecal samples from three calves of the Ameralik caribou population were examined for the presence of nematode eggs and eimerid oocysts. Two distinct nematode egg types were observed: the first, Nematodirella longissimespiculata, was found in all calves, while the second, a strongylid nematode, was detected in one calf. The coccidian eimerid Eimeria rangiferis was identified in all calves. This host-specific eimerid is found in Icelandic feral reindeer, which were also imported from Finnmark Norway. We suggest that Finnmark reindeer were the source of Eimeria rangiferis observed in Ameralik caribou today. There are three possible origins for the presence of N. longissimespiculata in Ameralik, 1) arrival with colonizing caribou from North America within the past 4000 years, 2) the 1952 introduction of semi-domesticated Norwegian reindeer, or 3) the current immigration of muskoxen.